Uncultured Gammaproteobacteria and Desulfobacteraceae Account for Major Acetate Assimilation in a Coastal Marine Sediment - Dyksma, Stefan; Lenk, Sabine; Sawicka, Joanna E.; Mußmann, Marc (Frontiers in Microbiology, 2018)
Acetate is a key intermediate in anaerobic mineralization of organic matter in marine sediments. Its turnover is central to carbon cycling, however, the relative contribution of different microbial populations to acetate assimilation in marine sediments is unknown. To quantify acetate assimilation by in situ abundant bacterial populations, we incubated coastal marine sediments with 14C-labelled acetate and flow-sorted cells that had been labelled and identified by fluorescence in situ hybridization. Subsequently, scintillography determined the amount of 14C-acetate assimilated by distinct populations. This approach fostered a high-throughput quantification of acetate assimilation by phylogenetically identified populations. Acetate uptake was highest in the oxic-suboxic surface layer for all sorted bacterial populations, including deltaproteobacterial sulfate-reducing bacteria (SRB), which accounted for up to 32% of total bacterial acetate assimilation. We show that the family Desulfobulbaceae also assimilates acetate in marine sediments, while the more abundant Desulfobacteraceae dominated acetate assimilation despite lower uptake rates. Unexpectedly, members of Gammaproteobacteria accounted for the highest relative acetate assimilation in all sediment layers with up to 31-62% of total bacterial acetate uptake. We also show that acetate is used to build up storage compounds such as polyalkanoates. Together, our findings demonstrate that not only the usual suspects SRB but a diverse bacterial community may substantially contribute to acetate assimilation in marine sediments. This study highlights the importance of quantitative approaches to reveal the roles of distinct microbial populations in acetate turnover.